Clay figurines, masks and animal-shaped vessels in children’s burials in Roman Imperial Africa - (:unkn) unknown (My University, 2014)
Clay figurative artefacts deposited in children’s burials in Roman Imperial Africa have mainly been found from the late nineteenth century onwards. Usually dissociated from their archaeological context, these items were well described in publications due to their figurative nature. An inventory of this material has been made and this catalogue allows us to analyse the function of this material based on a large quantitative database. The most common types and their geographical distribution have been highlighted. New excavations in North Africa provide well documented archaeological contexts and give new perspectives on this material through the analysis of the age of the deceased, location of artefacts in the tomb, associated gestures (breaking and reversal), association in the same burial. Multi-disciplinary analysis of these data has sometimes permitted a novel interpretation of the material. This new information and the various areas of research involved allow one to consider the role of these artefacts in African graves from different points of view and highlight regional peculiarities.
Keywords: African Research